Exploratory study on sequestration of some essential metals by indigo carmine food dye - Thalita Boldrin Zanoni; Arnaldo Alves Cardoso; Maria Valnice Boldrin Zanoni; Antonio Aparecido Pupim Ferreira (Universidade de São Paulo, 2010)
Indigo carmine forms a stable complex with different ions, and the stability constant of the complexes were evaluated as log K equal to 5.75; 5.00; 4.89 and 3.89 for complexes with Cu(II), Ni(II), Co(II) and Zn(II) ions, respectively, in 0.1 mol L-1 carbonate buffer solution at pH 10. The interaction between Cu(II) ions and indigo carmine (IC) in alkaline medium resulted in the formation of the Cu2(IC) complex, measured by the spectrophotometric method, with a stoichiometric ratio between indigo carmine and metal ions of 2:1 (metal-ligand). The reported method has also been successfully tested for determination of copper in pharmaceutical compounds based on copper-gluconate without pre-treatment. Índigo carmim forma complexos estáveis com diferentes íons e a constante de estabilidade dos complexos foi avaliada como log K igual 5,75; 5,00; 4,89 e 3,89, respectivamente, para os complexos com os íons Cu(II), Ni(II), Co(II) e Zn(II) em solução tampão carbonato 0,1 mol L-1, pH 10. A interação entre o íon Cu(II) e índigo carmin (IC) em meio alcalino resultou na formação do complexo Cu2(IC) monitorado por método espectrofotométrico, com razão estequiométrica entre o índigo carmim e o íon metálico de 2:1 (metal-ligante). O método relatado também tem sido testado com sucesso para determinação de cobre em compostos farmacêuticos à base de cobre-gliconato sem qualquer pré-tratamento.